Translating the Revolution: Otherness in Cuban Testimonial Literature - de Pedro Ricoy, Raquel (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Drawing on existing theories in the field, this paper seeks to explore the issues that surround the translation of Cuban testimonial texts, emphasizing the inevitable portrayal of the Self as an Other. The notion of translation as an articulation of otherness has become a focus of interest in contemporary translation studies. Notwithstanding the worth of the general framework that has emerged as a result, the need for country-specific research is underscored by Cuba’s unique location on the contemporary political map – and its alleged “exceptionalism” – which sets it apart from cultural contexts that have been previously studied. Because of the isolated nature of Cuba, it is important to highlight the gap between the Cuban literature that is published, translated and read outside Cuba, on the one hand, and the Cuban literature that is published and read in Cuba, on the other. The results of bibliographical research and fieldwork indicate that, although publishers and literary experts alike place great emphasis on the significance of otherness, their interest centres on the dissemination of the Cuban experience seen “from inside” (so as to counterbalance Cuban narratives produced by exiles). In doing so, they underscore the “universal nature” of the human experience and play down any alterity that may hinder the translation process.